The Pattern of Cardiac Disease at Coronary Care Unit of Dhaka Medical College Hospital (Cardiovascular Journal, 2015)
Background: Epidemiological transition which is taking place in every part of the world, among all races, ethnic groups and cultures has resulted in the global rise in cardiovascular disease (CVD). Cardiovascular disease is the leading cause of morbidity and mortality throughout the world. We tried to assess the pattern of cardiac disease at coronary care unit (CCU) of tertiary care hospital. Methods: A cross sectional study conducted among the patients admitted at CCU of Dhaka Medical College Hospital (DMCH) during the period of 1st January 2010 to 31st December 2010. A total of 2415 patients were included in the study. Results: A total 2415 patients in the year 2010, were admitted at CCU of DMCH, among them 56% (n=1346) were male and 44% (n=1069) were female. Out of total admitted patients 220 (9%) were below 30 years of age and 588 ( 24%) & 1607 (67 %) were the age group of 31 to 44 years and 45 years and above age group respectively. Among the disease group ischemic heart disease( IHD) (45%) was the most common cause of hospitalization followed by heart failure (HF) (16%) valvular heart disease (9%), hypertension (7%) and arrhythmia (2%). Acute myocardial infarction (30 %) was the leading cause of IHD followed by unstable angina (15%). Conclusion: This study has found that almost three-quarters of cardiac disease were due to IHD, HF and valvular heart disease in decreasing order of frequency. Countries like Bangladesh can be able to spend very little resources to address those cardiovascular diseases. Along with public as well as private sector efforts, public awareness about the risk factors for cardiovascular diseases should be improved to reduce this sort mortality and morbidity. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22259 Cardiovasc. j. 2015; 7(2): 119-122